PENGARUH PEMBERIAN PROBIOTIK DARI MIKROBA LOKAL TERHADAP PERFORMA AYAM PETELUR - Dani Priastoto; Tintin Kurtini; Sumardi . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The purpose of this research are to (1) determine the effect of probiotics on the local microbes on performance of layer; (2) determine the optimal level in the ration and IOFC of layer. This research do at 20thDesember 2014 – 19th Januari 2015 in CV Varia Agung Jaya Farm, Central Lampung. This research used a completely randomized design (CRD) using probiotic with 4 treatments (0, 1, 2 and 3%) with 5 replications with 2 chickens of is treatment which of the number of chickens that used was 40 chickens. The result of this research the giving probiotic from local microbal have significant effect on consumption and IOFC (P <0.05), whereas no significant effect on egg production, egg weight and feed conversion. Keywords : Probiotics, Performance, Layer